The Effect Of Entrepreneurship Lessons And Independent Attitude On Students' Entrepreneurial Motivation At State Vocational High School 1 Pakuan Ratu, Way Kanan District - Kurniawan, Edi; Umar Bakti; Rini Loliyani (ASIAN PUBLISHER, 2024)
This study aims to determine the effect of Entrepreneurship Lessons and Independent Attitudes on Student Motivation at SMKN 1 Pakuan Ratu, Way Kanan Regency. The type of data in this study uses quantitative research using primary and secondary data. In this study using probability sampling technique to determine the research sample because it has a population of over 100, the determination of the research sample using the slovin formula which obtained results of 59.67 rounded up to 60 respondents. The analysis technique used is through validity, reliability, classical assumptions and hypotheses tests. From the results of the research that has been done, it shows that Entrepreneurship Lessons and Independent Attitudes have a significant joint effect on the Entrepreneurial Motivation of Grade 2 students at SMK Negeri 1 Pakuan Ratu, Way Kanan Regency. Entrepreneurship Lessons and Independent Attitudes have an effect of 80.7% on the Entrepreneurial Motivation of grade 2 students of SMK Negeri 1 Pakuan Ratu, Way Kanan Regency. While the remaining 19.3% is influenced by other factors not examined in this study.